Rates and sources of nitrogen fertilizer application on yield and quality of Panicum maximum cv. Mombasa - Galindo, Fernando Shintate [UNESP]; Buzetti, Salatiér [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Dupas, Elisângela [UNESP] (My University, 2019)
The effects of nitrogen fertilizer sources (urea and ammonium nitrate) applied at different rates on the yield and quality of Megathyrsus maximus cv. Mombasa were compared in this study. The nitrogen rates applied after each monthly harvest were 0, 50, 100, 150 and 200 kg N/ha (i.e., 0, 150, 300, 450 and 600 kg N/ha/year). The N fertilizer sources did not affect the Mombasa grass response to any of the production and nutritional characteristics; however, increasing nitrogen rates there was significantly increased dry matter yield and crude protein percentage, and decreased neutral detergent fiber (NDF) concentrations. Dry matter yield in control treatments was 31.3 t/ha, and responses reached a maximum of 30% with the application of 150 kg N/ha/cut, but considering the economical rate, the better economic return occurs with the application of 115 kg N/ha/cut. As urea has a lower price per unit of N than ammonium nitrate, it seems to be the best choice of fertilizer. Further studies are needed to determine why the dry matter yields of forage were so high and in what seasons should N fertilizer be applied when resources are limited. Longer-term studies would confirm these findings and assess the losses of N to the atmosphere or by leaching, especially at the higher rates.
Efecto de dosis y forma de aplicación de fertilizante nitrogenado en el rendimiento y calidad de Panicum maximum cv. Mombasa
Keywords: Ammonium nitrate; Crude protein; Fertilizer responses; Guinea grass; Urea